1982
DOI: 10.1042/bj2060131
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynucleotide-interconverting enzymes and the quantification of deoxynucleoside triphosphates in mammalian cells

Abstract: We have demonstrated that methanol extracts of human cells are heterogeneous with regard to content of dNDP (deoxynucleoside diphosphate) and dNMP (deoxynucleoside monophosphate) kinases. The presence of these enzymes can affect the reliability of techniques used to measure intracellular pools of deoxynucleotides. An optimized extraction procedure and enzymic assay for dNTP species in haematopoietic cells are described which provide sensitivity to measure 0.1-40pmol of dATP, dTTP and dGTP, and 1.0-40pmol of dC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…1). Consistent with this function, numerous studies have reported that dNTP contents in cancer cells and transformed cell lines are elevated 3-10-fold compared with normal cells and that dividing cells have higher dNTP contents than non-dividing cells (1)(2)(3)(4)(5)(6). Cellular dNTP levels also fluctuate during the cell cycle and upon DNA damage, when replication and repair DNA synthesis levels are altered (6 -10).…”
mentioning
confidence: 65%
“…1). Consistent with this function, numerous studies have reported that dNTP contents in cancer cells and transformed cell lines are elevated 3-10-fold compared with normal cells and that dividing cells have higher dNTP contents than non-dividing cells (1)(2)(3)(4)(5)(6). Cellular dNTP levels also fluctuate during the cell cycle and upon DNA damage, when replication and repair DNA synthesis levels are altered (6 -10).…”
mentioning
confidence: 65%
“…Several studies have identifi ed available dNTP levels as a factor that can affect RT fi delity (Back and Berkhout, 1997;Vartanian et al 1997), yet very little research has been performed with HIV-1 RT fi delity mutations that occur naturally within infected hosts in the absence of HAART, despite the fact that cell types known to be targets for HIV-1 infection (e.g. macrophages, resting T cells, activated T cells) have variable dNTP pools (Traut, 1994;Diamond et al 2004;Hauschka, 1973;Fuller et al 1982;Skoog and Bjursell, 1974;Yao et al 2003). A recent study with SIV RT variants isolated from infected macaques demonstrated rapid selection against an RT variant with higher replication fi delity (Biesinger et al 2008).…”
Section: Viral Determinants Altering Phenotypementioning
confidence: 99%
“…Measurement of intraceflular nucleotide concentrations. Cells were extracted either by the perchloric acid precipitation method, followed by neutralization with 1 N KOH (34), or with 60% methanol for 24 h in the presence of 50 ,uM sodium tripolyphosphate (8). Nucleotides were separated and quantitated by highpressure liquid chromatography on a Partisil-Strong Anion Exchange (Whatman) column with ammonium phosphate buffers (pH 3.4) at a flow rate of 2.5 ml/min as the mobile phase, 10 mM for the nucleoside monophosphates, and 400 mM for the nucleoside triphosphates.…”
Section: Figmentioning
confidence: 99%